Profiling proteinuria in children after renal transplantation - Seeman, Tomás; Dusek, Jiri; Vondrák, Karel; Spatenka, Jaroslav; Feber, Janusz (Pediatric nephrology (Berlin, Germany), 2009)
Proteinuria is a common complication after renal transplantation (RTx). In adults, tubular proteinuria prevails and is associated with impaired graft survival. In the absence of studies on proteinuria profiling in transplanted children, we aimed at analyzing the types of proteinuria in transplanted children. Fifty-three children (11.8 years) were analyzed in a cross-sectional study. Morning urine was tested for total protein (PROT), albumin (ALB) and alpha-1-microglobulin (AMG). The type of proteinuria was assessed by the alpha-1-microglobulin/albumin algorithm (AAA): [AAA = AMG x 100/(AMG+ALB]. Median PROT, ALB, and AMG (in mg/mmol creatinine) were 20.0, 3.8, and 4.9, respectively. Pathological total proteinuria (>22 mg protein/mmol creatinine) was found in 47% of children (25/53). Only 20% of patients with pathological total proteinuria (5/25) had glomerular proteinuria, whereas 80% (20/25) had tubular proteinuria. Three of five children with glomerular proteinuria had chronic allograft nephropathy. Both AMG and albuminuria negatively correlated with the estimated glomerular filtration rate (eGFR) (p = 0.021 and 0.003, respectively). In conclusion, tubular proteinuria was present in 80% of children post-RTx and may be associated with impaired graft function; glomerular proteinuria is associated mainly with chronic allograft nephropathy.
Keywords: rejekce štěpu; Cross-Sectional Studies; algoritmy; albuminurie; Algorithms; transplantace ledvin; Česká republika; proteinurie; sérový albumin; Proteinuria; průřezové studie; Czech Republic; glomerulus; dítě; Child; ledvinové kanálky; Alpha-Globulins; Serum Albumin; Kidney Transplantation; Graft Rejection; Humans; Kidney Tubules; Transplantation, Homologous; alfa-globuliny; homologní transplantace; Albuminuria; Kidney Glomerulus; lidé